Effect of Plant Growth Regulators (IBA, BA, and CCC) on Some Vegetative Characters of Three Hybrid Lily Cultivars of (Lilium spp. L.) - A. Naji, Dhoha; J. Attiya, Hatim; M. Askar, Hassan (Iraqi Journal of Science, 2023)
The present study was conducted in the nursery of Floriculture Unit, University ofBaghdad in Iraq during September to December of 2013. Vernalized bulbs of hybrid lilycultivars were imported from the Netherlands. The experiments were included somehybrid lily cultivars which represent the main groups of lily (longiflorum hybrids,Asiatic hybrid and trumpet hybrids). The three lily cultivars named as Tiger (Oriental),Brunello (Asiatic) and White Heaven (Longiflorum) were sprayed two times, at fiveweeks after planting and at eight weeks after planting with a solution of Cycocel (100mg /l), solution of Indole butyric acid (50 mg/l) and Benzyl adenine (50 mg /l). Theresults indicated that foliar spray with IBA lead to increase in plant height, leaf number,leaf area, fresh weight of leaf and stem and dry weight of stem in Brunello. It increasedin plant height, leaf area, and fresh and dry weight of stem in White Heaven. TigerEdition increased in fresh and dry weight of the bulb while decreasing in dry weight bythe application of IBA. BA leads to increase in plant height, dry and fresh weight of aleaf, and leaf number in Brunello. It increased in dry weight of a leaf and bulb, and leafarea in Tiger Edition . Also increased in dry weight of stem and bulb, and fresh weightof bulb in White Heaven. While foliar spray with CCC lead to increase in leaf number,leaf area, dry weight of a leaf, dry and fresh weight of stem, and fresh weight of thebulb in Brunello. Dry weight of leaf, and dry and fresh weight of bulb increased in TigerEdition . Also lead to decrease in fresh weight of a leaf, and increase in fresh and dryweight of bulb in White Heaven. From these results, Brunello was more responsive toPGRs. CCC more PGRs was affected on lily cultivars.